Frequency of Positive Conversion of Interferon-Gamma Release Assay Results Among Patients With Inflammatory Bowel Disease Treated With Non-tumor Necrosis Factor Inhibitors - Kim, Kyuwon; Jo, Kyung-Wook; Shim, Tae Sun; Park, Jin Hwa; Hwang, Sung Wook; Park, Sang Hyoung; Yang, Dong-Hoon; Byeon, Jeong-Sik; Myung, Seung-Jae; Yang, Suk-Kyun; Ye, Byong Duk (Frontiers in Medicine, 2021)
Considering the risk of reactivation of latent tuberculosis infection (LTBI), not only before starting tumor necrosis factor inhibitors but also before non-TNF inhibitor therapy, LTBI screening is routinely recommended for patients with inflammatory bowel disease (IBD). However, data on the positive conversion of LTBI test results during non-TNF inhibitor therapy are scarce. Among IBD patients treated with vedolizumab and/or ustekinumab, a total of 91 patients who had negative baseline interferon-gamma release assay (IGRA) results, assessed by QuantiFERON®-TB Gold In-tube or QuantiFERON®-TB Gold Plus, were enrolled. Serial LTBI test results after starting non-TNF inhibitor therapy were collected, and patients’ clinical characteristics were analyzed. Positive IGRA conversion was observed in six of 91 patients (6.6%). The cumulative IGRA conversion–free survival rates after starting therapy were 97.7% after 1 year and 86.7% after 2 years. Ulcerative colitis was more common among converters compared with non-converters (66.7% vs. 23.5%, P = 0.040). Among six converters, four had been treated with vedolizumab, one with ustekinumab, and the other with vedolizumab followed by ustekinumab. All six patients had been previously exposed to TNF inhibitors before non-TNF inhibitor therapy: five to infliximab and one to both infliximab and adalimumab. After positive IGRA conversion, none of the six converters developed active tuberculosis while maintaining non-TNF inhibitor therapy (median 6.8 months, range 0.4–32.1 months). Positive IGRA conversion among IBD patients treated with vedolizumab and/or ustekinumab appears to occur somewhat frequently, but its clinical implications remain to be elucidated.